2021
DOI: 10.1002/cam4.3941
|View full text |Cite
|
Sign up to set email alerts
|

Response to first‐line treatment predicts progression‐free survival benefit of small‐cell lung cancer patients treated with anlotinib

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…After reading the full-text of the remaining 19 studies, 6 of them were further excluded as they were ongoing clinical trials and/or clinical trial designs. Finally, the remaining 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] were included for this meta-analysis. The process of literature screening is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the full-text of the remaining 19 studies, 6 of them were further excluded as they were ongoing clinical trials and/or clinical trial designs. Finally, the remaining 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] were included for this meta-analysis. The process of literature screening is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In this meta-analysis, there were 8 retrospective studies with single arms, [18][19][20][21][22]25,26,28 3 retrospective studies 17,24,29 with two arms, and 2 RCTs 23,27 with anlotinib versus control arms. This meta-analysis involved 779 patients.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Therefore, it is important to screen the benefit population of anlotinib treatment by methods. Recently, three retrospective studies about SCLC treatment with anlotinib had tried to select some ways to identify those benefit patients, which indicated that the response to first‐line treatment, 22 prognostic nutritional indexes, 11 and tumor cavitation 9 could predict survival independently, yet all through relatively simple means. Our team once established a system of risk scores by different combinations of multiple inflammatory indicators in NSCLC, which was capable of predicting the best population for anlotinib treatment 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The PFS resulting from this research was similar to another related retrospective study (mPFS: 2.6 months). 9 However, while Recently, three retrospective studies about SCLC treatment with anlotinib had tried to select some ways to identify those benefit patients, which indicated that the response to first-line treatment, 22 prognostic nutritional indexes, 11 and tumor cavitation 9 could predict survival independently, yet all through relatively simple means.…”
Section: Discussionmentioning
confidence: 99%
“…The ALTER-0303 phase III randomized clinical trial confirmed the effectiveness and safety of anlotinib as a third-line treatment in patients with NSCLC (Han et al, 2018). It was reported that anlotinib could improve the survival of patients diagnosed with advanced lung cancer, either NSCLC or small-cell lung cancer (SCLC) (Li et al, 2021;Qin et al, 2021). A real-world study conducted by Zhang K. et al (2020) also confirmed the efficacy and safety of anlotinib in advanced NSCLC patients.…”
Section: Introductionmentioning
confidence: 88%